Base promoted direct C4-arylation of 4-substituted-pyrazolin-5-ones with diaryliodonium salts1. Issue 46 (23rd May 2015) - Mao, Song; Geng, Xu; Yang, Yang; Qian, Xiaofei; Wu, Shengying; Han, Jianwei; Wang, Limin
<x xml:space="preserve">Abstract</x> A metal-free approach for the C4-arylation of 4-substituted-pyrazolin-5-ones with diaryliodonium salts was developed.